2017
DOI: 10.1128/jvi.00498-17
|View full text |Cite
|
Sign up to set email alerts
|

Virological Control by the CD4-Binding Site Antibody N6 in Simian-Human Immunodeficiency Virus-Infected Rhesus Monkeys

Abstract: Passive immunotherapy against HIV-1 will most likely require broadly neutralizing antibodies (bnAbs) with maximum breadth and potency to ensure therapeutic efficacy. Recently, the novel CD4 binding site antibody N6 demonstrated extraordinary neutralization breadth and potency against large panels of cross-clade pseudoviruses. We evaluated the in vivo antiviral activity of N6-LS, alone or in combination with the established V3-glycan antibody PGT121, in chronically simianhuman immunodeficiency virus (SHIV)-SF16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 44 publications
1
41
0
2
Order By: Relevance
“…Similarly, removal of a PNGS adjacent to the CD4bs (N276 gp120 ) reduced sensitivity to the gp120-gp41 interface bNAb 8ANC195 (Scharf et al, 2014) but had no effect on 1-18 ( Figure 4). V H -restricted CD4bs bNAbs typically interact with loop D residues N279 gp120 and/or N280 gp120 , and changes in these residues have been associated with viral rebound from CD4bs therapy (Diskin et al, 2013;Horwitz et al, 2013;Julg et al, 2017;Klein et al, 2012;Lynch et al, 2015a). When we tested HIV-1 YU2 variants with mutations at these residues, we observed reduced or abrogated sensitivity to VRC01-class bNAbs and to the V H 1-46-derived CD4bs bNAb 8ANC131 (Figure 4).…”
Section: -18 Is Not Affected By Typical Vrc01-class Escape Mutationsmentioning
confidence: 99%
“…Similarly, removal of a PNGS adjacent to the CD4bs (N276 gp120 ) reduced sensitivity to the gp120-gp41 interface bNAb 8ANC195 (Scharf et al, 2014) but had no effect on 1-18 ( Figure 4). V H -restricted CD4bs bNAbs typically interact with loop D residues N279 gp120 and/or N280 gp120 , and changes in these residues have been associated with viral rebound from CD4bs therapy (Diskin et al, 2013;Horwitz et al, 2013;Julg et al, 2017;Klein et al, 2012;Lynch et al, 2015a). When we tested HIV-1 YU2 variants with mutations at these residues, we observed reduced or abrogated sensitivity to VRC01-class bNAbs and to the V H 1-46-derived CD4bs bNAb 8ANC131 (Figure 4).…”
Section: -18 Is Not Affected By Typical Vrc01-class Escape Mutationsmentioning
confidence: 99%
“…For example,nearly all HIV-1 variants found in recent plasma samples from the original VRC01 donor are now resistant to VRC01 [42], as are the VRC01-resistant strains we previously identified in a chronically infected patient [39][40][41].Similar to what we found in the current study, the mutations responsible for such resistance are also confined to the area between residues 278 and 283 of Loop D, and to potential N-linked glycosylation sites between residues 458 and 467 of the β23/loop V5/β24 region. Analyses of rebound viruses in humanized mice or rhesus macaque models after antibody monotherapy with 3BNC117 and N6 also revealed mutations between 279-281 of loop D, and between 458-459 of the β23/loop V5/β24 region [44,45] In particular,human monotherapy trials with the 3BNC117 and VRC01 antibodies revealed significant polymorphisms. A shift in HIV-1 plasma RNA populations was found at the abovementioned positions ( Fig 6).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the superior potency and breadth of these CD4bs bnAbs, each fails to neutralize a small but significant portion of pseudotyped virus panels [17,25,27,28,37,38].For instance, VRC01 is unable to neutralize about 10% of tested viruses [25], and resistant strains have been isolated from patients infected with subtype B, subtype C, CRF07_BC, and CRF08_BC [29,[39][40][41][42]. Furthermore, reports show thatVRC01-, 3BNC117-and N6-resistant strains have emerged in both animal models and human clinical trials [11,15,[43][44][45][46][47], indicating that resistant virus Broadly resistant HIV-1 against CD4bs antibodies PLOS Pathogens | https://doi.org/10.…”
Section: Author Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…The recent identification of highly potent and broadly neutralizing antibodies (bNAbs) against HIV-1 has led to a renaissance of antibodies as therapeutic and prophylactic tools. Initial preclinical and clinical studies with passive administration of bNAbs have shown great promise that these monoclonals could play a revolutionary role in HIV care (3)(4)(5)(6)(7)(8)(9). While these antibodies are able to temporarily reduce plasma viral loads in viremic HIV-1-infected individuals (3,5,10) or delay viral rebound once ART is stopped, recent studies showed that neutralization-resistant viral strains were often selected to emerge, ultimately resulting in virological failure of bNAb treatment (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%